The impact of the indonesian nickel industry downstreaming policy especially - Ali Martin; Ismiyatun Ismiyatun; Saadatul Musthoifiyah (Indonesian Institute For Counseling, Education and Therapy, 2026)
This study examines the impact of Indonesia's nickel industry downstreaming policy, focusing on Morowali Regency, Central Sulawesi. Employing a qualitative library research method, the study analyzes Foreign Direct Investment theory regarding market access, raw material utilization, and technology transfer to explain both positive and negative consequences of the policy. Findings reveal that downstreaming generates a substantial multiplier effect, including employment absorption, regional economic growth, and MSME expansion, particularly through companies such as PT GNI. Conversely, the policy produces severe negative impacts, including environmental damage, discharge of nickel waste into coastal waters, and landscape transformation. The study concludes that government and stakeholders must prioritize environmental protection, waste management, reforestation, and local worker employment, rather than focusing solely on mining profits, to ensure sustainable and balanced industrial development in nickel-producing regions.